Peningkatan Sistem Informasi Manajemen Untuk Menerapkan Oprasional Terintegrasi Pada UMKM - Jusmawati Jusmawati; Fahad Hisyam; Dera Andani; Citra Anisa Tika Putri (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to explain the role of management information systems to implement integrated operations in MSMEs. With integrated data, MSME actors get an overall picture of the performance of which information systems need to be improved. Through this integration system, it also allows MSMEs to connect various buyers by facilitating better collaboration and coordination. The results of the implementation of the management information system (MIS) MSMEs get better operational coordination, centralized data management, accurate analysis reporting, reduced operational costs and increased customer satisfaction